A Convenient Synthesis and Antimicrobial Activity of Functionalized 1,2,4-Triazoles and 3-Amino-alkyltetraazabicyclo[3.3.0]octan-8-ones - Sulaiman Al-Ayed, Abdullah; Mohamed Dridi, Khaireddine (Asian Journal of Chemistry, 2013)
5-Amino-1,2,4-triazole derivatives and their bicyclic system were synthesized in moderate to good yields from the corresponding a-aminoesters, hydrazine or methylhydrazine and the starting material dimethyl N-cyanodithioiminocarbonate. Many target compounds were obtained. But, in cases when the bicyclic system is not formed, 5-amino-1,2,4-triazoles are usually formed. Structures of the prepared compounds were elucidated on the basis of their spectral data and their antifungal and antibacterial activities were also evaluated.